Design, Characterization and Evaluation of Metallic Nano Biocomposites of Neomycin - Swathi, Vottikuti; Vidyavathi, Maravajhala; Prasad, T.N.V.K.V.; Kumar, R.V. Suresh (Journal of Applied Solution Chemistry and Modeling, 2013)
Neomycin is formulated into nanoparticles in order to increase the therapeutic efficacy, decrease the dose of drug and to decrease the topical dose related toxic effects. The present study was aimed at the preparation of zinc nanoparticles (ZN), chitosan nanoparticles (CN), zinc neomycin nanoparticles (ZNN) and zinc chitosan neomycin nanoparticles (ZCNN) in order to compare their antibacterial activity. Nanoparticles were prepared by subjecting the nano suspension containing the specified ingredients to stirring at 40oC for 4-5 h. The prepared nanoparticles were evaluated for particle size and surface morphology by Transmission Electron Microscopy (TEM), mean particle size and particle size distribution by DLS, percentage yield, loading efficiency, in vitro drug release by diffusion technique and agar cup plate method. TEM microphotographs and zeta sizer analysis revealed that the prepared nanoparticles were in the nanometric range, the particle size and particle size range of ZCNN was less compared to ZNN indicated more surface area of ZCNN. Among all the nanoparticles prepared, percentage yield, loading efficiency, in vitro drug release and zone of inhibition was found to be more for ZCNN. Thus, the results suggested that ZCNN act as promising drug delivery systems with better in vitro characteristics compared to other nanoparticles with increased therapeutic activity of neomycin.